Histopathological study of the influence of platelet rich-plasma and low level laser therapy on healing of experimentally fractured proximal sesamoid bone in equine: Sinan A ; M J Eesa and Raffal A. Omar - Eesa, M. J. (The Iraqi Journal of Veterinary Medicine, 2017)
The objective of this study was to evaluate the effects of platelet rich plasma and low level laser therapy (diode laser) on the healing of proximal sesamoid bone fracture. Eighteen healthy adult donkeys were divided into three equal groups: First group was used as control group, second group was treated by platelet rich plasma and the third group treated by diode laser. Also each group was divided to two equal subgroups according to period of postoperative macroscopical, histopathological examination: (one and three months post operation). All animals were exposed experimentally to transverse mid body fracture of lateral proximal sesamoid bone, in control group the bone fixed internally by screw and followed by external fixation with Plaster of Paris under general anesthesia, the second and third groups were exposed to similar surgical procedure except in second group injected of autologous platelet rich plasma in the fracture site, and the third group exposed to serial session of low level laser. All experimental animals were in a good health postoperatively, except hyper granulation tissue was observed in one animal belongs to the first group and another one belongs to the second group exhibited superficial exudates at the site of operation. Histopathological examination showed connective tissues and thin bone trabecular filling the fractured gap in first group at one month postoperatively, whereas, the bone trabecular was replaced by compact bone at three months postoperatively. Moreover lamellar bone and thick compact bone formation were seen at one month in third group, as well as to a lesser degree in the second group; however the fractured gap was filled with compacted bone mainly at three months postoperativelyin third group. In conclusions, both laser and platelet rich plasma were enhanced healing of the proximal sesamoid bones fracture but the superiority of better healing was occurred by laser treatment.